The underground movement in Austria : what the underground anti-nazi struggle is really like : a sober and informed account of revolutionary organisation under nazism - Czernetz, Karl (London : National Labour Press Controversy Publishing Co., 1942)
Bibliotheek Camille Huysmans
Themanummer van "Left", april 1942 nr 67
Engels
Brochure
Keywords: Wereldoorlog 2; Oostenrijk